Factors that Influence the Learning Achievement of Students Majoring in Accounting at the Institut Teknologi dan Bisnis Master Pekanbaru - Alfat, Fanni Fadilah (Reflection: Education and Pedagogical Insights, 2024)
This research aims to determine the influence of internal factors and external factors on the learning achievement of students majoring in accounting at the Master's Institute of Technology and Business. This research is expected to provide evidence that internal factors and external factors can influence whether or not the learning achievement of students majoring in accounting. The population of this research were all students majoring in accounting at the Pekanbaru Masters Institute of Technology and Business. This research method uses a quantitative method by collecting questionnaire data which is distributed to respondents. The sample for this research consisted of 57 respondents from students majoring in accounting at the Pekanbaru Master's Institute of Technology and Business. The data analysis technique used is multiple linear regression. The results of this research showed that the influence of internal factor variables on learning achievement in part obtained a coefficient value of -0.030 with a statistical t test value of -0.266 with a significance of 0.791. Based on the significance value of t, it shows that at the 5% level internal factors do not have a significant effect on the learning achievement of students majoring in accounting. External factors have a significant effect on student learning achievement with a coefficient of 0.598 with a t test of 5.330 and a significance of 0.000. Based on the significance value of t, it shows that at the 5% level external factors have a significant effect on the learning achievement of students majoring in accounting. Internal factors and external factors influence simultaneously, the higher the internal factors and external factors, the more they influence student learning achievement.